Proposed ripplon induced weak localization of electrons over liquid helium - Dahm, A.J. (Физика низких температур, 1997)
Ripplon-induced weak localization is proposed for electrons on a liquid-helium surface. Ripplon scattering is quasi-elastic, the ripplons are quasi-static relative to the electron velocity, and the relative change in occupation number of the ripplon state in a scattering event is small. Conditions for the observation of ripplon-induced weak localization are calculated.